O contato linguístico português e espanhol na fronteira Brasil-Argentina: crenças e atitudes linguísticas - Kusy, Adriane (2019)
Our objective with the present work is to describe linguistic beliefs and linguistic attitudes from the speech of informants in Portuguese and Spanish language contact situation on the border between Brazil and Argentina. For our database we selected the cities of Dionísio Cerqueira, in Brazil, and Bernardo de Irigoyen, Argentina, with a dry border, where walking between sides is free. In each one of them eight informants will be selected according to criteria of Multidimensional and Relational Dialectology. For the elaboration and accomplishment of this work, will be followed the theoretical and methodological principles of the Multidimensional and Relational Dialectology (Thun 1998; 2005; 2010) which contemplates the variational space in different dimensions and in its varied correlations of data. For data collection we used a part of the metalinguistic questionnaire of the project Atlas of Languages in Contact at the Frontier (2013), adapted to the reality of the informants, which contemplates questions about languages and their users, as well as free conversations and notes on the field notebook. Thus, we verify linguistic beliefs and linguistic attitudes from implicit measures to assess the link between linguistic attitudes and linguistic behavior. From the data obtained, it was possible to analyze how is the behavior and linguistic uses of individuals living in this border region between the contact of Portuguese and Spanish. It was found that even though all informants believe that learning the other's language is important, it is clear that Portuguese is much more used on the Argentinean side than Spanish on the Brazilian side.